Centrofacial Balamuthiasis: case report of a rare cutaneous amebic infection. (12th July 2016) - Chang, Oliver H.; Liu, Fan; Knopp, Eleanor; Muehlenbachs, Atis; Cope, Jennifer R.; Ali, Ibne; Thompson, Robert; George, Evan
Abstract : Free‐living amebae are ubiquitous in our environment, but rarely cause cutaneous infection. Balamuthia mandrillaris has a predilection for infecting skin of the central face. Infection may be restricted to the skin or associated with life‐threatening central nervous system (CNS) involvement. We report a case of a 91‐year‐old woman, who presented with a non‐healing red plaque over her right cheek. Several punch biopsies exhibited non‐specific granulomatous inflammation without demonstrable fungi or mycobacteria in histochemical stains. She was treated empirically for granulomatous rosacea, but the lesion continued to progress. A larger incisional biopsy was performed in which amebae were observed in hematoxylin‐eosin stained sections. These were retrospectively apparent in the prior punch biopsy specimens. Immunohistochemistry and polymerase chain reaction studies identified the organisms as Balamuthia mandrillaris . Cutaneous infection by B. mandrillaris is a rare condition that is sometimes complicated by life‐threatening CNS involvement and which often evades timely diagnosis due to its rarity and nonspecific clinical manifestations. Moreover, these amebae are easily overlooked in histopathologic sections because of their small number and their resemblance to histiocytes. Dermatopathologists should be familiar with the histopathologic appearance of these organisms and include balamuthiasis and other amebic infections in the differential diagnosis of granulomatous dermatitis.